PENGARUH KOMPETENSI, OBJEKTIVITAS, DAN TEKANAN ANGGARAN WAKTU TERHADAP KUALITAS HASIL AUDIT PERWAKILAN BPKP SULAWESI UTARA - Lohonauman, Hans; Sondakh, Jullie J.; Kalalo, Meily Y. B. (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
This study aims to determine the influence of competence, objectivity, and time budget pressure on the quality of audit results BPKP North Sulawesi Representative. The population used in this study is the BPKP auditor. Method of sampling by purposive sampling according to predetermined criteria. The number of samples collected was 45 respondents. The research data is the primary data obtained directly from the research object. The collected data is analyzed by using data analysis which is done by testing the data quality and classical assumption before doing hypothesis testing. Hypothesis testing in this study using multiple linear regression analysis with t test, f test, and coefficient of determination. The results of this study indicate that the variables of competence and objectivity have a significant effect on the quality of audit results. This shows that competence and objectivity affect the quality of audit results. While the time budget pressure had no significant effect on the quality of audit result. This suggests that time budget pressure does not affect the quality of audit results.Keywords : competence, objectivity, time budget pressure, and quality of audit results